2022
DOI: 10.1080/24740527.2022.2059754
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the transition from acute to chronic postsurgical pain in youth: A narrative review of epidemiologic, perioperative, and psychosocial factors

Abstract: A growing number of studies have identified high rates of pediatric chronic postsurgical pain (CPSP) after major surgery. Pediatric CPSP is associated with pain-related distress and comorbid mental health outcomes, such as anxiety and depression. From a biopsychosocial perspective, youth factors, such as genetics, epigenetics, sex, presurgical pain, sleep, anxiety, and pain catastrophizing, as well as parent factors, such as cognitive appraisals of their child’s pain expression and pain catastrophizing, conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…3,17,81,83,85 Despite the heterogeneity in measurements and number of trajectories identified, the finding of distinct pain recovery pathways has been replicated in many pediatric and adult studies. 18,80,100,101 Prospective studies examining acute and chronic postoperative pain trajectories have shown that the majority of children undergo normal recovery with decreasing surgical pain over time. However, there is a subset of patients classified into cohorts with high or severe pain that persists or increases over time.…”
Section: Postoperative Pain Trajectoriesmentioning
confidence: 99%
“…3,17,81,83,85 Despite the heterogeneity in measurements and number of trajectories identified, the finding of distinct pain recovery pathways has been replicated in many pediatric and adult studies. 18,80,100,101 Prospective studies examining acute and chronic postoperative pain trajectories have shown that the majority of children undergo normal recovery with decreasing surgical pain over time. However, there is a subset of patients classified into cohorts with high or severe pain that persists or increases over time.…”
Section: Postoperative Pain Trajectoriesmentioning
confidence: 99%
“…In sum, previous studies have identified several risk factors for the development of CPSP, among them symptoms of anxiety, preoperative pain intensity and poorer sleep quality as well as parental catastrophising, even though the results were equivocal in part. 5 6 40 The extent to which emotion-related factors can serve as resilience factors has had minimal investigation in the transition from acute to CPSP. 5 Further, the promotion of resilience mechanisms as a prevention strategy has had limited focus in the context of paediatric chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“… 5 6 40 The extent to which emotion-related factors can serve as resilience factors has had minimal investigation in the transition from acute to CPSP. 5 Further, the promotion of resilience mechanisms as a prevention strategy has had limited focus in the context of paediatric chronic pain. 7 41 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally to these recently published studies, the bio-molecular mechanisms of the transition from acute to CPSP are described in three comprehensive reviews 6,95,96▪▪ . This review focuses on adults; for comprehensive reviews on children and adolescents, see refs 96▪▪–99▪ .…”
Section: Introductionmentioning
confidence: 99%